Multi-Field Collaborative of Oil-Immersed Transformer for Distributed Energy Resources Temperature Rise Considering the Influence of Heat Transfer Oil - Huang, Kun; Li, Hua; Wang, Wei; Zhang, Lifeng; Feng, Anhui; Li, Xiaohua (Frontiers in Energy Research, 2021)
The current calculation method of fluid–structure interaction (FSI) has a defect for oilimmersed transformers for distributed energy resources (DERs). In order to solve this problem, a calculation method is proposed for the temperature rise of oil-immersed transformers in this article. The vibration of insulating oil is considered in this method. Different from the temperature field model established by FSI, the effect of insulating oil vibration on the temperature field is considered. The structure field is introduced to establish the insulating oil vibration model. The temperature field correction coefficient is introduced by coupling the insulating oil vibration and the natural convection of the insulating oil. The result shows that compared with FSI, the results of the calculation method in this study are consistent with the experiment, and the temperature field distribution in the oil-immersed transformer can be calculated more accurately.